2015
DOI: 10.1101/033886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fitness effects of new mutations inChlamydomonas reinhardtiiacross two stress gradients

Abstract: Most spontaneous mutations affecting fitness are likely to be deleterious, but the strength of selection acting on them might be impacted by environmental stress. Such stress-dependent selection could expose hidden genetic variation, which in turn might increase the adaptive potential of stressed populations. On the other hand, this variation might represent a genetic load and thus lead to population extinction under stress. Previous studies to determine the link between stress and mutational effects on fitnes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 48 publications
6
13
0
Order By: Relevance
“…By accommodating explicitly for individual nonheritable variation in longevity, the measurable genotype fitness becomes dependent on the strength of selection which may vary between environments. This trend is common in data (Kraemer, Morgan, Ness, Keightley, & Colegrave, 2016), but the reverse has also been observed (Kishony & Leibler, 2003) and occurs in our framework when mutants are less variable than their ancestors (Figure 4b,d,f). First, we assume that the phenotypic variance of the ancestor is negligible compared to the mutant and find this to result in measurable fitness ratios (solid colored lines in Figure 4a,c,e) that are consistently lower than those that would have resulted from the same mean effects if mutant and ancestor had the same variance (dashed lines), a discrepancy that increases with stress.…”
Section: Rel Ative Fitne Ss Defined Along S Tre Ss G R Ad Ientssupporting
confidence: 86%
“…By accommodating explicitly for individual nonheritable variation in longevity, the measurable genotype fitness becomes dependent on the strength of selection which may vary between environments. This trend is common in data (Kraemer, Morgan, Ness, Keightley, & Colegrave, 2016), but the reverse has also been observed (Kishony & Leibler, 2003) and occurs in our framework when mutants are less variable than their ancestors (Figure 4b,d,f). First, we assume that the phenotypic variance of the ancestor is negligible compared to the mutant and find this to result in measurable fitness ratios (solid colored lines in Figure 4a,c,e) that are consistently lower than those that would have resulted from the same mean effects if mutant and ancestor had the same variance (dashed lines), a discrepancy that increases with stress.…”
Section: Rel Ative Fitne Ss Defined Along S Tre Ss G R Ad Ientssupporting
confidence: 86%
“…Specifically, some studies have shown that larger declines in fitness are experienced in harsher environments, while others have not (Martin and Lenormand 2006;Halligan and Keightley 2009;Kraemer et al 2015). In M9MM+CAA and M9MM, we can statistically distinguish fitness effects from s = 0 with greater precision (s , -0.03 in M9MM +CAA and s , -0.01 or s .…”
Section: Discussionmentioning
confidence: 87%
“…These lineages accumulate mutations independently over several thousand generations, and the magnitude and variance in fitness between lineages can be used to estimate several properties of the distribution of fitness effects (Halligan and Keightley 2009). MA studies have been used to characterize the fitness effects of spontaneous mutations in Drosophila melanogaster (Bateman 1959;Mukai 1964;Keightley 1994;Fry et al 1999), Arabidopsis thaliana Shaw et al 2000Shaw et al , 2002, Caenorhabditis elegans (Keightley and Caballero 1997;Vassilieva et al 2000;Estes et al 2004;Katju et al 2015), Saccharomyces cerevisiae (Wloch et al 2001;Zeyl and de Visser 2001;Dickinson 2008;Jasmin and Lenormand 2015), Escherichia coli (Kibota and Lynch 1996;Trindade et al 2010), and other microbes (Heilbron et al 2014;Kraemer et al 2015). Results from these studies have occasionally been inconsistent, but the majority of results suggest that most spontaneous mutations have mild effects (Eyre-Walker and Keightley 2007;Halligan and Keightley 2009;Agrawal and Whitlock 2012;Heilbron et al 2014), that deleterious mutations far outnumber beneficial mutations (Keightley and Lynch 2003;Eyre-Walker and Keightley 2007;Silander et al 2007), and that the distribution of effects of deleterious mutations is complex and multimodal (Zeyl and de Visser 2001;Eyre-Walker and Keightley 2007).…”
mentioning
confidence: 99%
“…To further investigate the effect of stress on mutational effects, we conducted competitive fitness assays in medium supplemented with 2.5 g/L NaCl, representing moderate stress (Kraemer et al. ). Moderately stressful conditions represent a more realistic scenario for environmental conditions that might be encountered by new mutants, in contrast to nearly lethal conditions.…”
Section: Resultsmentioning
confidence: 99%